Perancangan Furnitur dan Elemen Dekoratif pada Gereja Bethel Indonesia Perumnas Mojosongo, Jebres, Surakarta - Agustin, Felycia; Setiawan, Andreas Pandu; Nilasari, Poppy Firtatwentyna (Intra, 2019)
Religion is considered as one of the basic needs in today's modern world living. Basic human needs nowadays are in fostering, enhancing, and developing the mental, spiritual state of the mind that can be found in the Church. The church is a building where Christians do worship, one of which is in the Indonesian Bethel Church, especially in the Perumnas area of Mojosongo, Jebres, Surakarta. The Church building is not only used to fulfill human spiritual needs, but is also used for academic purposes. Hence, in order to maximize the function of the building, it requires interior products and decorative elements which of course are based on the ergonomics that will provide comfort and support the people who are carrying out activities in the building.